The Impact of Brand Image on Laptop Purchasing Intention —The Moderating Role of Consumer Ethnocentrism - WU, Lingceng; QU, Yi; ZHAO, Shuo; ZHOU, Shu (International Journal of Business, Economics and Management, 2022)
This paper aims to analyze the influence of laptop brand image on the purchasing intention of Chinese college students, and it further looks at the moderating role played by consumer ethnocentrism in the above causality, which helps to bridge the research gap in the domain. Employing the brand image theory and consumer ethnocentrism theory, and based on large-sample questionnaire surveys, this study reveals that brand image positively affects college students’ purchasing intention of laptops, regardless of domestic or foreign laptop brands. What is more, besides playing a direct role in affecting purchasing intention, consumer ethnocentrism also plays a significant moderating role in affecting the effects of brand image on purchasing intention. It is found that high ethnocentric college students may not buy foreign laptops, even though the brand image of foreign laptops is superior. Overall, this paper has made important suggestions and implications for both corporate managers and policy makers.